(3GdEWGQ GdfXQj hGdeeGQSI GdJWHjbjIs - (3WhGgQ eMeO(B, (3GdJgGejs; (3eSYhO(B, (3UOjbjs ((3GdLRGFQ (B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2005)
(3eGgjI GdeQGLYI(B- (3eYGjjQ GdeQGLYI(B- (3GdeHGOF GdeMGSHjI(B- (3fXGe GdQbGHI GdOGNdjI(B- (3ebheGJ fXGe GdQbGHI GdOGNdjI(B- (3ELQGAGJ fXGe GdQbGHI GdOGNdjI(B- (3GdELQGAGJ GdYedjI ddeQGLYI(B- (3Jbjje fXGe GdQbGHI GdOGNdjI(B- (3OQGSI GdMGdI(B.s
(3GdeQGLY U(B.193s
Keywords: (3GdeQGLYIs; (3GdfXGe GdeMGSHjs; (3JObjb GdMSGHGJs